Fontes de gordura e óleo essencial de orégano na dieta de bovinos: fermentação ruminal e produção de metano - Pinto, Thays Matias da Silva (Universidade Federal do Tocantins, 2023)
Lipid supplementation and the use of essential oils as additives in diets for cattle are an alternative to increase the energy density of the diet and reduce the production of gases by the ruminant. Thus, the present study aimed to evaluate in vitro the effect of using oregano fat and essential oil in bovine diets to improve rumen fermentation and mitigate methane production. The evaluated diets were composed of concentrate, corresponding to 90% of the dry matter, containing cornmeal, the respective source of fat, plus 10% of the roughage DM, Megathyrsus maximus cv. Mombasa. The randomized experimental design contained six treatments in a factorial arrangement (3x2), in which three diets were used: standard, with protected fat and with soybean oil, with the inclusion or not of oregano essential oil. Three cattle were used to collect the ruminal inoculum. The inoculum was removed using an esophageal tube and then taken to the laboratory. Measurements of gas production were performed at times of 3; 6; 9; 12; 15; 19; 24; 30; 36; 48; 72 and 96 hours after the start of in vitro incubation. The measurement of methane was through the 5 mL portion of collected gas, injected into a TEC-GA21BIO® portable gas analyzer. When the ruminal fermentation kinetics were observed, there was a greater production of gases with the treatment with protected fat and the inclusion of oregano oil, and the opposite effect in the standard treatments with only 90% concentrate and 10% forage. Ruminal gas production was higher in treatments using protected fat and oregano essential oil. And the degradation of dry and organic matter present superior results for treatments using protected fat. Methane production was lower in treatments with oregano essential oil inclusion. Thus, the best responses were obtained with diets with the inclusion of oregano essential oil.